Generating Local Economic Potential as Efforts to Develop Undeveloped Areas in Kulon Progo Regency - Rosita Hidayatullah (Journal of Economic and Business Analysis, 2024)
This study examines the strategies for developing underdeveloped areas in efforts to improve social welfare, particularly in Kulon Progo Regency. Kulon Progo Regency, like many other regions in Indonesia, faces challenges in harnessing local economic potential to enhance well-being in underdeveloped areas. This research aims to explore strategies that can be employed to stimulate local economic potential as a step towards more sustainable development in these areas. Qualitative research methods are used to gain in-depth insights into the local economic situation and the challenges faced by the people of Kulon Progo. The findings indicate that there is a diverse range of local economic potentials that can be utilized, such as agriculture, forestry, and fisheries. However, there are still barriers such as market access, limited infrastructure, and a lack of access to capital and technology. Therefore, collaborative efforts between the government, communities, and the private sector are needed to develop strategies that can maximize the utilization of local economic potential. Implementing supportive programs, training, and financing that address local needs can be an initial step in enhancing local economic potential and developing underdeveloped areas in Kulon Progo Regency.